2020
DOI: 10.1371/journal.pmed.1003284
|View full text |Cite
|
Sign up to set email alerts
|

Severe mental illness and health service utilisation for nonpsychiatric medical disorders: A systematic review and meta-analysis

Abstract: Background Psychiatric comorbidity is known to impact upon use of nonpsychiatric health services. The aim of this systematic review and meta-analysis was to assess the specific impact of severe mental illness (SMI) on the use of inpatient, emergency, and primary care services for nonpsychiatric medical disorders. Methods and findings PubMed, Web of Science, PsychINFO, EMBASE, and The Cochrane Library were searched for relevant studies up to October 2018. An updated sear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 109 publications
5
35
0
Order By: Relevance
“…As the EPA guidance recommend, the psychiatrist and the general practitioner should play an active role in the assessment and management of cardiovascular risk factors, as an integral part of the care of their psychiatric patients [4]. Difficulties experienced by people with severe mental disorders in accessing general medical services contribute to reduced life expectancy (Lawrence & Kisely, 2010) [57,40]. Several studies demonstrated underutilization of health care services, especially specialized care services, by psychiatric patients [40][41][42], particularly by patients with schizophrenia.…”
Section: Statement 3 10 11: Coordination Of Cardiometabolic Risk Asmentioning
confidence: 99%
See 1 more Smart Citation
“…As the EPA guidance recommend, the psychiatrist and the general practitioner should play an active role in the assessment and management of cardiovascular risk factors, as an integral part of the care of their psychiatric patients [4]. Difficulties experienced by people with severe mental disorders in accessing general medical services contribute to reduced life expectancy (Lawrence & Kisely, 2010) [57,40]. Several studies demonstrated underutilization of health care services, especially specialized care services, by psychiatric patients [40][41][42], particularly by patients with schizophrenia.…”
Section: Statement 3 10 11: Coordination Of Cardiometabolic Risk Asmentioning
confidence: 99%
“…Difficulties experienced by people with severe mental disorders in accessing general medical services contribute to reduced life expectancy (Lawrence & Kisely, 2010) [57,40]. Several studies demonstrated underutilization of health care services, especially specialized care services, by psychiatric patients [40][41][42], particularly by patients with schizophrenia. To ensure standards of care and to avoid further stigmatization of these patients [43], psychiatrists should facilitate patients' access to primary and specialized somatic health care services and collaborate with primary care physicians, endocrinologists, and cardiologists to ensure accurate follow-up of patients' health care.…”
Section: Statement 3 10 11: Coordination Of Cardiometabolic Risk Asmentioning
confidence: 99%
“…Moreover, suffering from both mental and physical disorders has complex and bidirectional characteristics. When a mental disorder is accompanied by a mental or physical problem, it has been reported that the patient suffered from exacerbated symptom burden, functional disability, reduced quality of life, higher cost, and more medical service use [6][7][8][9][10]. Prevalence of comorbidities is high among those with mood disorders including depression and anxiety disorders [5].…”
Section: Introductionmentioning
confidence: 99%
“…It is difficult to estimate the proportion of people who had a mental disorder with a comorbidity, and even if it is reported, the criteria used for symptom classification vary by country [6,11,12]. Registration of medical comorbidity is an important research domain, which is related to survival [13], and various studies have been attempted.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation